Development of Simple-Sequence Repeats Markers from Durian (Durio zibethinus Murr. cultv. Matahari) Genomic Library - Panca Jarot Santoso; Adi Pancoro; Sony Suhandono; I Nyoman Pugeg Aryantha (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Simple sequence repeats have been proved as powerful markers and widely used in molecular breeding to reduce cycles and cost efective. The availability of the marker is, however, very limited in durian. This research aimed to develop SSR markers from durian genomic library. Genomic DNA was isolated from durian shoot leaf, whilst SSR motifs were isolated using membrane-based oligonucleotide enrichment hybridization protocol. Annotation made on the library found 527 unique motifs from 354 durian libraries which form 425 loci. The SSR motifs obtained were generally short repeats which reached 89.6 %, whilst longer repeats were found consisted of compound motifs. Eleven loci were selected as representative for further test to prove their informativity. A number of unique allels were successfully amplified from 17 durian genomes. The analysis showed the polymorphic information content (PIC) values ranged from 0.000 to 0.662 with an average of 0.390. The SSR loci also showed their ability to be used for durian diversity analysis as the evident that the loci could be used as genetic markers for assisting further durian breeding program.